Digital athletics in analogue stadiums: Comparing gratifications for engagement between live attendance and online esports spectating. Issue 3 (7th January 2020) - Sjöblom, Max; Macey, Joseph; Hamari, Juho
Abstract : Purpose: Esports (electronic sports) are watched by hundreds of millions of people every year and many esports have overtaken large traditional sports in spectator numbers. The purpose of this paper is to investigate spectating differences between online spectating of esports and live attendance of esports events. This is done in order to further understand attendance behaviour for a cultural phenomenon that is primarily mediated through internet technologies, and to be able to predict behavioural patterns. Design/methodology/approach: This study employs the Motivation Scale for Sports Consumption to investigate the gratifications spectators derive from esports, both from attending tournaments physically and spectating online, in order to explore which factors may explain the esports spectating behaviour. The authors investigate how these gratifications lead into continued spectatorship online and offline, as well as the likelihood of recommending esports to others. The authors employ two data sets, one collected from online spectators ( n =888), the other from live attendees ( n =221). Findings: The results indicate that online spectators rate drama, acquisition of knowledge, appreciation of skill, novelty, aesthetics and enjoyment of aggression higher than live attendees. Correspondingly, social interaction and physical attractiveness were rated higher by live attendees. Vicarious achievement and physical attractiveness positively predicted intention to attend live sports events while vicarious achievement and novelty positively predicted future online consumption of esports. Finally, vicarious achievement and novelty positively predicted recommending esports to others. Originality/value: During the past years, esports has emerged as a new form of culture and entertainment, that is unique in comparison to other forms of entertainment, as it is almost fully reliant on computer-human interaction and the internet. This study offers one of the first attempts to compare online spectating and live attendance, in order to better understand the phenomenon and the consumers involved. As the growth of esports is predicted to continue in the coming years, further understanding of this phenomenon is pivotal for multiple stakeholder groups.